On the authenticity of the Lithuanian compound proper name stem gerd- - Sinkevičiūtė, Daiva (Baltistica, 2017)
This article deals with the issue of authenticity of the Lithuanian compound proper name stem gerd- and the proposal presented is that the stem gerd- is a secondary variant of gird- that arose in the process of writing Lithuanian onyms in Old Russian and Polish documents.
Keywords: Lithuanian; onomastics; personal name; onym; compound proper name; compound proper name abbreviation; stem; surname